2010
DOI: 10.1097/brs.0b013e3181d7a197
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Serum Chromium Levels After Stainless Steel Posterior Spinal Instrumentation for Adolescent Idiopathic Scoliosis

Abstract: After adjusting for the number of years since surgery, metal implant exposure is positively associated with elevated serum chromium levels in adolescent idiopathic scoliosis patients with stainless steel posterior spinal implants. This is the first study to identify statistically significant positive associations between specific spinal implant characteristics (other than corrosion identified by radiographs) and serum chromium levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Studies of metal ion levels in patients with spinal implants are less numerous. There have been only a few retrospective reports of metal ion levels in patients with stainless steel [18][19][20][21][22] and titanium [23,24] posterior spinal instrumentation. Less is known for metalon-metal total disc arthroplasty [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of metal ion levels in patients with spinal implants are less numerous. There have been only a few retrospective reports of metal ion levels in patients with stainless steel [18][19][20][21][22] and titanium [23,24] posterior spinal instrumentation. Less is known for metalon-metal total disc arthroplasty [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…A study by del Rio et al [19] described similarly elevated serum nickel and chromium levels in patients with instrumented spinal arthrodesis, noting the correlation between significantly higher metal ion levels and radiological signs of device corrosion. Rackham et al [21] determined that the number of metal connections/interfaces was positively correlated with serum chromium levels in a group of 30 patients undergoing posterior spinal arthrodesis.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that this novel mobile-head screw shows high-level durability and histological safety; however, as the serum titanium level increased to 2-3 times the preimplantation control level, sufficient follow-up is considered necessary. It is known that the concentrations in the metal serum increase by size and the number of internal implants [13]. Also, though the long-term course is unknown, it is reported that the concentrations in the metal serum do not increase gradually at least with age [14].…”
Section: Discussionmentioning
confidence: 99%
“…Also concerning, recent studies have demonstrated elevated chromium levels in patients who have had fusion with stainless steel implants 73 and that these levels appear to be related to the amount of material used during fusions 74 . The implications of higher chromium levels are unknown, but high levels in animals have carcinogenic and mutagenic effects.…”
Section: Spinementioning
confidence: 99%
“…The implications of higher chromium levels are unknown, but high levels in animals have carcinogenic and mutagenic effects. Long-term follow-up is needed, although chromium levels do appear to decrease over time 74 .…”
Section: Spinementioning
confidence: 99%